Stochastic gene expression: bacterial elites in chemotaxis - Simon van Vliet; Martin Ackermann (Molecular Systems Biology)
Abstract Even in the absence of genetic or environmental differences, cells differ from each other in their molecular make‐up. The consequences of these phenotypic differences are often not well understood. New work by Waite et al (2016) directly links variation in the molecular composition of individual bacterial cells to their population‐level performance.